National Common Curricular Base: implications for the Early Childhood curriculum in the State of Paraná (Olhar de Professor, 2023)
The Common National Curricular Base for Early Childhood Education (BNCCEI) and the Paraná Curricular Reference of Early Childhood Education (RCPEI), together with the National Curricular Guidelines for Early Childhood Education - DCNEI's, constitute the documents that regulate the development of the curricula for this educational stage. The present article analyzes the context, the elaboration, and the theoretical and methodological basis of these documents, to identify their implications for the Early Childhood Education curricula of Paraná's municipalities. To do so, it adopts a qualitative approach and uses the methodological procedures of bibliographic research, document analysis, and literature review. This study is driven by the assumptions of the normative curriculum (GOODSON, 2013) and DCNEIs. It was concluded that the BNCCEI and the RCPEI reiterate important concepts presented by the DCNEIs in their theoretical and methodological texts. However, they present divergences concerning learning and development objectives, which sometimes refer to a prescriptive and schooling logic.
Keywords: Preschool Education. Common National Curricular Basis. Paraná Curriculum Reference.